Legal but lethal: functional protein aggregation at the verge of toxicity - Falsone, Angelika; Falsone, S. Fabio (Frontiers in Cellular Neuroscience, 2015)
Many neurodegenerative disorders are linked to irreversible protein aggregation, a process that usually comes along with toxicity and serious cellular damage. However, it is emerging that protein aggregation can also serve for physiological purposes, as impressively shown for prions. While the aggregation of this protein family was initially considered exclusively toxic in mammalians organisms, it is now almost clear that many other proteins adopt prion-like attributes to rationally polymerise into higher order complexes with organised physiologic roles. This implies that cells can tolerate at least in some measure the accumulation of inherently dangerous protein aggregates for functional profit. This review summarises currently known strategies that living organisms adopt to preserve beneficial aggregation, and to prevent the catastrophic accumulation of toxic aggregates that frequently accompany neurodegeneration.